LIBRARY OUTREACH STRATEGIES IN INCREASING USER PARTICIPATION IN PUBLIC LIBRARIES: A LITERATURE STUDY - Bangun, Muhammad Farid; Anjani, Nabbila Indra; Anjani, Putri Zulfati Wardina (PERSPEKTIF: Journal of Social and Library Science, 2025)
This study identifies that the growth of social media and the development of new technologies create significant opportunities for libraries to reach a broader audience. However, this also presents challenges, particularly among teenagers who tend to spend more time using their phones and interacting on social media platforms rather than reading or accessing literacy resources. Nevertheless, libraries can leverage social media as a tool to promote their services, expand the reach of information, and create interactive spaces that foster reading habits. This study also highlights the importance of libraries in supporting the development of information literacy skills, especially among higher education students. Through various creative approaches, such as establishing book clubs, providing user- centered learning spaces, offering virtual help desks, and using social media, libraries can actively contribute to improving access to information while encouraging reading habits among young people. Moreover, libraries have a significant influence on users' reading behavior by offering relevant collections, comfortable spaces, and innovative programs. To meet the ever-evolving expectations of users, libraries must continuously develop innovative outreach strategies. This includes integrating digital technology, organizing community-based activities, and collaborating with other institutions to enhance their impact on society. This study emphasizes that libraries can play a strategic role in advancing information literacy by remaining relevant to users' needs in the digital age. Thus, libraries can act as agents of change, supporting lifelong learning and strengthening the culture of literacy within communities. By adapting to technological advances and user demands, libraries can ensure their continued relevance and effectiveness in fulfilling their mission to educate, engage, and inspire.